Aces high 10 of the best Air Ace Library comic books ever! - Holland, Stephen (Air Ace picture library, 2009)
First launched in 1958, the War Picture Library produced numerous battle stories, but perhaps their most popular were those featuring the adventures of the warriors of the air. The flyers were seen as the glamour boys of World War II-they handled the most sophisticated and technically advanced combat machines ever invented-and there was almost limitless scope to develop stories based around their exploits. The machines they flew-including fighters such as Spitfires, Hurricanes, Messerschmitts, Mustangs, and Zeros-were lovingly recreated by the finest artists. The 10 stories featured in this exciting collection include tales of a flak-blasted night sky over Germany and a twisting and turning Typhoon with a Focke-Wulf in its sights. The included images are reproduced 25 percent larger than in their original published form.